Palladium-Catalysed Direct Heteroarylations of Heteroaromatics Using Esters as Blocking Groups at C2 of Bromofuran and Bromothiophene Derivatives: A One-Step Access to Biheteroaryls - Fu, Hai Yan; Zhao, Liqin; Bruneau, Christian; Doucet, Henri (Synlett, 2012)
Methyl 5-bromo-2-furoate and ethyl 5-bromothiophene-2-carboxylate have been found to be useful alternative reagents to 2-halofurans and 2-halothiophenes for the palladium-catalysed direct arylation of heteroaromatics. As their C5 is blocked by ester groups, the use of these substrates prevents the formation of dimers or oligomers, and therefore allows the formation of biheteroaryls in high yields. A very wide variety of heteroaromatics can be coupled with these two reagents. Moreover, with methyl 5-bromo-2-furoate, sequential catalytic C5 arylation, decarboxylation, catalytic C2-arylation reactions allowed the synthesis of 2,5-diarylated furan derivatives.
Keywords: methyl 5-bromo-2-furoate; ethyl 5-bromothiophene-2-carboxylate; palladium; direct arylation; heteroaromatics; biheteroaryls